The synthesis of ortho-fused cycloocta-2,5-dien-1-one cores and their derivatisation - Eccleshare, Lee (2017)
Eight-membered rings are notoriously difficult to synthesise due to unfavourable transannular and conformational strain within the ring system. That being said, there are many biologically active natural products that contain such ring systems. For instance, potent anti-cancer compound Taxol®, has an eight-membered ring at its core. Many contemporary synthetic routes to 8-membered rings require the use of complex cyclisation precursors, due to the difficulties associated with the formation of 8-membered rings. The synthesis of such precursors commonly include multiple steps, with each step consuming researcher time, effort and resources. Described herein is new methodology that can be used to synthesise eight-membered carbocyclic cores, in a one-pot, single step synthesis from easily attainable starting materials. A novel Cannizzaro triggered cascade allowed swift formation of eight-membered rings from three components without the need to synthesise, purify and characterise unwanted intermediates. The key step in the cascade is a Cannizzaro-like 1,5-hydride transfer that simultaneously forms a carbanion and powerfully Michael accepting ynone. Annulation is achieved through the reaction of these centres. Application of this methodology led to the synthesis of 30 novel ortho-fused eight-membered carbocycles, in up to 81% yield. Utilisation of a ‘temperature switch’, based on competition of kinetic and thermodynamic pathways, enabled the synthesis of 7 novel 1,2-dihydronaphthalen-1-ol or naphthalene cores. The mechanisms of the aforementioned transformations have also been probed both experimentally and computationally to support our proposed mechanism. With the aim of synthesising a diverse library of 8-membered ring derivatives, the Cannizzaro cascade was extended to enable trapping of a reactive intermediate with electrophiles. A Diversity Oriented Synthetic project was undertaken using the products of the 3- and 4-component cascade reaction as starting points to build molecular diversity. In a maximum of three-steps, from commercial bromo-aldehydes, we have been able to develop a library of compounds that contain; four-, five-, six-, eight- and nine-membered ring systems; nitrogen, sulfur and oxygen containing heteroaromatics; bicyclic and tricyclic fused-ring systems; and functional groups including a carboxylic acid, amides, lactams, alcohols, ketones, halogens, nitriles, esters, oximes, alkenes, alkynes, enones and a pyrazalone ring. Representative examples from this library have been through a limited number of biological screening assays and have shown biological activity in two different areas. It was found that some compounds in this library are able to stimulate the secretion of Glucagon-like Peptide-1, a possible target for the treatment of type II diabetes.